2011
DOI: 10.1074/jbc.m110.204024
|View full text |Cite
|
Sign up to set email alerts
|

PKCα Mediates β-Arrestin2-dependent Nephrin Endocytosis in Hyperglycemia

Abstract: Nephrin, the key molecule of the glomerular slit diaphragm, is expressed on the surface of podocytes and is critical in preventing albuminuria. In diabetes, hyperglycemia leads to the loss of surface expression of nephrin and causes albuminuria. Here, we report a mechanism that can explain this phenomenon: hyperglycemia directly enhances the rate of nephrin endocytosis via regulation of the ␤-arrestin2-nephrin interaction by PKC␣. We identified PKC␣ and protein interacting with c kinase-1 (PICK1) as nephrin-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 34 publications
4
83
0
3
Order By: Relevance
“…Indeed, we found that the diabetes-induced increase in glomerular PKC-α expression was attenuated in diabetic podNox4KO mice. Quack et al have demonstrated that acute hyperglycaemia increases nephrin endocytosis in a PKC-α-dependent manner [45] and this effect is considered to promote albuminuria. In this study, we found similar changes in VEGF and nephrin expression as well as in albuminuria, in diabetic podNox4KO mice to those seen in diabetic PkcαKO mice, and also noted a reduction in glomerular PKC-α expression in podNox4KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that the diabetes-induced increase in glomerular PKC-α expression was attenuated in diabetic podNox4KO mice. Quack et al have demonstrated that acute hyperglycaemia increases nephrin endocytosis in a PKC-α-dependent manner [45] and this effect is considered to promote albuminuria. In this study, we found similar changes in VEGF and nephrin expression as well as in albuminuria, in diabetic podNox4KO mice to those seen in diabetic PkcαKO mice, and also noted a reduction in glomerular PKC-α expression in podNox4KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Upon VEGF-A binding, VEGFR2 autophosphorylation at Tyr-1175 mediates PLC␥ binding, leading to PKC activation (19,21,22). Interestingly, PKC␣ mediates the effect of hyperglycemia on nephrin-␤-arrestin2 interaction, increasing nephrin endocytosis in podocytes (45,46). PKC␣ negatively regulates VEGF signaling and endothelial nitric oxide synthase phosphorylation in endothelial cells (53).…”
Section: Discussionmentioning
confidence: 99%
“…Nephrin was the first globulin transmembrane protein found specifically on the SD of podocytes and is important in maintaining slit integrity [18][19]; therefore, nephrin serves as an early marker of podocyte damage [20]. In nephrin knockout mice, podocyte foot processes disappear, SD are deformed and excess proteinuria occurs.…”
Section: Discussionmentioning
confidence: 99%